Keywords: Performance, Employees Kinerja Pegawai Negeri Sipil Pada Satuan Polisi Pamong Peraja di Kabupaten Melawi: Kinerja Pegawai Negeri Sipil Pada Satuan Polisi Pamong Peraja di Kabupaten Melawi - Nikodimus, Nikodimus (Universitas Kapuas Sintang, 2025)
Abstract: Performance is a very important and fundamental thing for Civil Servants in carrying out their duties and is an obligation that has been given to them. Without high discipline and awareness from employees, the tasks carried out will not be completed properly and smoothly, which in the end the organization's goals will not be achieved. Based on the results of research related to the discipline of working hours for Civil Servants in the Melawi Regency Government, the legal provisions that serve as guidelines in determining working days and hours are the Melawi Regent Regulation Number 25 of 2011 concerning the Development of Civil Servant Discipline in the Melawi Regency Government, In the Melawi Regent Regulation Number 25 of 2011 concerning the Development of Civil Servant Discipline in the Melawi Regency Government, as stated in Article 3 paragraph 2. This study concludes that the Melawi Regency Civil Service Police Unit has shown good discipline in working hours, this can be seen from the indicators of discipline and consistency in carrying out duties and the regent's regulations regarding working hours for Civil Servants including Sat Pol PP. Suggestions or recommendations that can be formulated related to this research are that the government should be able to pay attention to Sat Pol PP, because of the large role and function of Sat Pol PP towards the discipline of all civil servants in the Melawi Regency Government.